2020
DOI: 10.2147/opth.s281860
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Profile of <em>HLA-B27</em>-Associated Uveitis in an Egyptian Cohort</p>

Abstract: Purpose To describe the clinical profile of patients with HLA-B27-associated uveitis at 2 Egyptian tertiary eye centers. Methods A retrospective study reviewing the medical records of all patients with HLA-B27-associated uveitis served at 2 uveitis referral clinics in Egypt between January 2010 and June 2018. Results The study included a total of 554 patients. Anterior uveitis was the most common type. Ankylosing spondylitis was an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 44 publications
2
3
3
Order By: Relevance
“…However, this data is significantly influenced by the study design and the prevalence of the HLA-B27 allele in the general population, reported as 8% in the Caucasian population from western countries and 1–5% in Africa, Asia, and Arabia [ 7 ]. Regarding sex distribution, previous studies conducted in Cuba [ 19 ], Egypt [ 18 ], and Colombia [ 11 ] reported a higher prevalence in males representing 56.5, 68.2 and 79.2% of cases, respectively, that contrasts with our findings since 59% of our patients were female. As for the age of onset, HLA-B27-associated uveitis patients are commonly described as young individuals between their 20' to 40' [ 7 , 20 ].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, this data is significantly influenced by the study design and the prevalence of the HLA-B27 allele in the general population, reported as 8% in the Caucasian population from western countries and 1–5% in Africa, Asia, and Arabia [ 7 ]. Regarding sex distribution, previous studies conducted in Cuba [ 19 ], Egypt [ 18 ], and Colombia [ 11 ] reported a higher prevalence in males representing 56.5, 68.2 and 79.2% of cases, respectively, that contrasts with our findings since 59% of our patients were female. As for the age of onset, HLA-B27-associated uveitis patients are commonly described as young individuals between their 20' to 40' [ 7 , 20 ].…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, the anatomical diagnosis is often described as only anterior. Nonetheless, 17.9% of our patients had vitreous involvement, with 15.4% having a combined anterior and intermediate uveitis presentation; this strongly contrasts with the study done by Abd El Latif et al [ 18 ], who reported vitreous involvement in only 6.5% of their patients, and Monnet et al [ 23 ] who reported vitritis in 10.3% of their patients. In the context of recurrences, our findings are different from those reported by Power et al [ 24 ], with an average number of recurrences of 3.6 (2–22) in contrast to our 1.5 and 1.42 mean of recurrences in six and twelve months.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations